1997
DOI: 10.1172/jci119608
|View full text |Cite
|
Sign up to set email alerts
|

Do beta-chemokines have clinical relevance in HIV infection?

Abstract: The role of ␤ -chemokines in HIV infection was evaluated. The kinetics of regulated upon activation of normal T cell expressed and secreted, macrophage inflammatory protein-1 ␣ , and macrophage inflammatory protein 1 ␤ production by stimulated T lymphocytes did not differ substantially between HIV-infected (asymptomatic and with AIDS) and uninfected subjects. Maximal production of these ␤ -chemokines by activated peripheral blood cells was higher in the infected individuals than in uninfected individuals, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 48 publications
(48 reference statements)
3
40
1
Order By: Relevance
“…For example, the kinetics of induced ␤-chemokine (MIP-1␣, MIP-1␤, RANTES) secretion are no different between HIV-1-infected or -uninfected individuals, at least in in vitro bulk cultures of activated CD4 ϩ or CD8 ϩ T cells [99]. However, the maximal (total) production of these ␤-chemokines was higher in HIV-1-infected than HIV-1-uninfected individuals, although among HIV-1-positive patients, there was no difference between the levels produced by asymptomatic patients versus those with clinical AIDS [99,100]. In fact, several studies have shown no correlation between long-term nonprogression and ␤-chemokine levels either in serum or from cultured PBMCs [101,102].…”
Section: Chemokine/chemokine Receptor Axes In Aids Pathogenesis Chemomentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the kinetics of induced ␤-chemokine (MIP-1␣, MIP-1␤, RANTES) secretion are no different between HIV-1-infected or -uninfected individuals, at least in in vitro bulk cultures of activated CD4 ϩ or CD8 ϩ T cells [99]. However, the maximal (total) production of these ␤-chemokines was higher in HIV-1-infected than HIV-1-uninfected individuals, although among HIV-1-positive patients, there was no difference between the levels produced by asymptomatic patients versus those with clinical AIDS [99,100]. In fact, several studies have shown no correlation between long-term nonprogression and ␤-chemokine levels either in serum or from cultured PBMCs [101,102].…”
Section: Chemokine/chemokine Receptor Axes In Aids Pathogenesis Chemomentioning
confidence: 99%
“…Because both CD4 and CD8 cells secrete ␤-chemokines, it may be the local concentration of ␤-chemokines that may be relevant for inhibiting R5 viral entry. It is interesting to note that HIV-1 infection itself modulates ␤-chemokine secretion: HIV-1-infected CD4 ϩ T cells as well as monocyte/macrophage cultures showed a marked elevation in ␤-chemokine production, however, this was only elicited by infection with R5 and not X4 viruses [48,99]. On the other hand, infection of ex vivo cultured human lymphoid tissue by X4 and not R5-viruses up-regulated ␤-chemokine production [104].…”
Section: Chemokine/chemokine Receptor Axes In Aids Pathogenesis Chemomentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of chemokines required for anti-HIV activity appears to be much higher than the physiologic amount generally found in HIV-infected people (11). It is also curious that R5 viruses induce a greater production of ␤-chemokines than do the X4 viruses (22).…”
mentioning
confidence: 99%
“…Increased levels of ␤-chemokines have been shown to inhibit HIV infection (34). HIV infection induces ␤-chemokine productions (12,35,36), which presumably play a crucial role in recruiting uninfected T cells and monocytes to sites of active viral replication (35). Thus, differential expression of ␤-chemokines may contribute to the observed difference in susceptibility of CM and CMDM to HIV infection.…”
Section: Discussionmentioning
confidence: 99%